Answer:
Yes they ate Equivalent
Step-by-step explanation:
Given the expression
h(x) = - 3x – 1;j(x) = – 7x + 11 ; k(x) = 21.22 – 262 – 11
H(x)•j(x) = (-3x-1)(-7x+11)
H(x)•j(x) = (-3x)(-7x)-3x(11)-1(-7x)(-1)(11)
H(x)•j(x) = 21x²-33x+7x-11
H(x)•j(x) = 21x²-26x-11
This shows that H(x)•j(x) = k(x)
log(4) + log(2) - log(5)
= log(2²) + log(2) - log(5)
= 2 log(2) + log(2) - log(5)
= 3 log(2) - log(5)
= log(2³) - log(5)
= log (2³/5)
= log (8/5)
= log (1.6) = 0.2041... (rounded)
Answer:
4/27
Female:15/27 female with an A:4/15
Male:12/27 male with an A:3/12
Answer=15/27 ×4/15
Combine like terms:
3x-2>5x+10 becomes -12 > 2x
Dividing both sides by 2, we obtain x < -6
Answer:
1/4 is the number
a.k.a. 0.25
Step-by-step explanation:
Replace the words "a number" with x
4x + 2 = 3
Then, simplify
4x = 1
x = 1/4